Circular bioeconomy practices and their associations with household food security in four RUNRES African city regions - Sekabira, H.; Feleke, S.; Manyong, V.; Spath, L.; Krutli, P.; Simbeko, G.; Vanlauwe, B.; Six, J. (2024)
Achieving the United Nation’s 2030 agenda which aims, among other goals, to ensure sustainable consumption and production patterns, requires a sustainable resource use model deployed at scale across global food systems. A circular bioeconomy (CBE) model of resource use has been proposed to reuse of organic waste in agricultural production to enhance food security. However, despite several initiatives recently introduced towards establishing a CBE in sub-Saharan Africa (SSA), minimal scientific efforts have been dedicated to understanding the association of CBE practices and food security. This study use data from 777 smallholder farm households from DRC, Ethiopia, Rwanda, and South Africa, to examine associations between three CBE practices (use of organic waste as compost, as livestock feed, and sorting waste) and household food security. Using different regression and propensity score matching models (PSM). Result reveal that using CBE practices more likely adds a 0.203 score of food insecurity access prevalence (HFIAP), 1.283 food insecurity access scale (HFIAS-score) and 0.277 for household dietary diversity score (HDDS) among households using CBE practiced groups. Associations regarding using organic waste as compost are generally positive but insignificant, while those with sorting waste are significantly and consistently negative. Thus, CBE innovations aiming to enhance household food security could prioritize organic waste valorization into livestock feed consider socio economic aspects such as access to land, access to market, education level, using mobile phone, income and city regions where interventions took place. However, prior sorting of waste is necessary to enable effective waste valorization.